Analisis Tantangan Dan Peluang Terhadap Pengembangan Produk Halal Olahan Hasil Laut Di Kecamatan Klampis Kabupaten Bangkalan - Luluk Luthfiyah; Trischa Relanda Putra; Eni Sri Rahayu Ningsih (GLOBAL SCIENTS PUBLISHER, 2024)
Klampis District, which is located in Bangkalan Regency, has great potential in the seafood processing industry considering its location is very close to the sea, especially in meeting the demand for halal products. The focus of this research includes the challenges faced by producers in developing halal products, producers' knowledge and awareness of the importance of halal certification in the production process, analysis of opportunities that can be utilized by producers to develop products that are competitive in the market, as well as analysis of strategies that can be applied to overcome challenges and exploit opportunities in product development. This research aims to analyze the challenges and opportunities in developing halal processed seafood products in Klampis District, Bangkalan Regency. Through the right strategy, processed seafood products from this area have a great opportunity to develop and contribute more significantly to the local economy. This research uses a descriptive qualitative research method with a case study approach. The research was conducted through interviews with local producers and participant observation to collect data from the local community. The output target that the author chose is to publish the results of this research through scientific publications in accredited national journals.